A Case Controlled Trial Comparing Biologic Therapy vs. Immunomodulators in Moderate-to-Severe Crohn’s Disease - Syed Osama Talat, Zahoor Ahmed Shah, Jahanzaib, Rakhshanda Naheed, Javeria Sarfraz, Javaria Zafar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Moderate-to-severe Crohn’s disease (CD) remains therapeutically challenging, with escalatingcosts and variable outcomes between biologic and immunomodulator (IMM) strategies. Thepresent case-controlled trial enrolled 120 adult patients with active